Symbolic and Aesthetic Representation of the Royal Carriage as a Manifestation of Palace Craft Art: Implications for the Study of Cultural Identity in the Archipelago - Wahyono; Guntur; Suyanto; Eko Supriyanto (PANGGUNG, 2025)
Craft art represents a cultural expression reflecting community creativity, identity, and skills. In Indonesia, craft art has a long historical tradition influenced by Hindu-Buddhist, Islamic, and European colonial cultures. One prominent manifestation of palace craft art is the royal carriage (kereta kencana), which serves as ceremonial transportation and a symbol of royal authority, social status, and cultural identity. This study investigates the royal carriage's aesthetic, symbolic, and technical representations as a significant artifact of palace craft art. The research adopts a qualitative approach through literature study, relying on written sources such as books, scientific articles, and historical documents. Findings indicate that the royal carriage reflects exceptional aesthetic quality and technical mastery through high-quality materials such as teak wood, precious metals, luxurious textiles, and intricate carvings, integrating elements of Hindu-Buddhist, Islamic, and Western cultures. Symbols such as Garuda, Arabic calligraphy, floral and faunal motifs, and Baroque ornaments represent the royal institutions’ philosophical, spiritual, and political values. Nevertheless, this research has limitations regarding the empirical exploration of symbolic meaning shifts in modern contexts. Further studies are recommended to employ ethnographic approaches, material analyses, and conservation strategies utilizing digital technology and artisan regeneration to maintain the relevance of palace craft heritage as a critical part of Indonesia’s cultural identity.